Continuous fiber reinforced prepreg tape and preparation method thereof
By combining the air-flow yarn spreading method with the segmented impregnation technology, the problems of uneven fiber spreading and low resin impregnation efficiency are solved, the Y-axis strength and weather resistance of the prepreg tape are improved, and high-quality prepreg tape production is achieved.
Patent Information
- Application Number
- CN202511205217.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-27
AI Technical Summary
Traditional fiber-reinforced prepreg tapes have problems such as uneven fiber expansion, low resin impregnation efficiency, complex process parameter coupling, and poor prepreg performance. In particular, the strength improvement in the Y-axis direction is limited and the weather resistance is insufficient.
The air flow yarn spreading method is combined with the segmented impregnation technology. The carbon fiber is pretreated and modified, and the fiber is non-contact spread using high-pressure airflow. Combined with the segmented impregnation treatment and the use of modified impregnation materials, the fiber distribution and resin bonding are optimized to form uniform polar link points, enhance the Y-axis link effect, and improve the performance of the resin material through chemical modification.
The uniform expansion and efficient impregnation of the fibers are achieved, and the comprehensive mechanical properties and weather resistance of the prepreg tape are improved. In particular, the tensile strength in the Y-axis direction is significantly improved, and the overall performance is better than commercially available products.
Smart Images

Figure SMS_2 
Figure SMS_4 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of prepreg tape production, and in particular relates to a continuous fiber reinforced prepreg tape and a preparation method thereof. Background Art
[0002] Fiber-reinforced resin-based composites can be divided into two categories based on the properties of the resin matrix: thermosetting resin-based composites and thermoplastic resin-based composites. Thermosetting resin-based composites have inherent disadvantages, such as low fracture toughness and damage tolerance, poor moisture absorption and environmental adaptability, long processing cycles, and difficulty in recycling, which limit their development and application. Thermoplastic resin-based composites, on the other hand, have the following advantages: 1. Good toughness, high fatigue strength, and high impact damage tolerance; 2. Unlimited storage life for fiber prepregs and sheet molding materials; 3. Good thermoforming processability, short molding cycles, and high production efficiency; 4. Scrap or waste can be remelted and molded or recycled, making them environmentally friendly. Therefore, thermoplastic composites are attracting increasing attention and have become a research and development hotspot in the field of composite materials.
[0003] The traditional prepreg production process faces a series of technical bottlenecks that need to be addressed. First, uneven fiber deployment is a prominent issue. During the fiber tow deployment stage, the tension distribution is difficult to precisely control, leading to localized accumulation or loosening. This phenomenon directly negatively impacts the uniformity of subsequent impregnation, threatening the quality of the final product. Second, inefficient resin infusion is a major challenge. The relatively simple flow channel structure of existing impregnation molds hinders the molten resin from penetrating the fiber bundle, making it difficult to achieve fully uniform penetration. The result is often dry spots on the prepreg or fluctuations in the resin content, seriously affecting the product's performance and quality stability. Furthermore, the coupling between process parameters is extremely complex. Multiple key parameters, such as pulling speed, resin viscosity, and temperature, are interdependent and mutually influential. Failure to precisely control these parameters can lead to poor prepreg performance and stability, making it difficult to meet high-quality production requirements.
[0004] Research has been conducted on improving the uniformity of prepreg fiber deployment by combining air-spinning technology. However, this research has found that while this method effectively improves the product's key performance, namely the tensile strength along the X-axis (the axial direction of the long fibers) and significantly improves impregnation uniformity and efficiency, it also shows limited or even poor performance in the prepreg's Y-axis (perpendicular to the axial direction of the long fibers). Furthermore, the prepreg's weather resistance remains limited. Summary of the Invention
[0005] The technical solution of the present invention addresses the problems of uneven fiber expansion, low resin impregnation efficiency, complex process parameter coupling, etc. in traditional fiber reinforcement solutions, as well as the defects of some poor performance in new yarn spreading and dipping technologies. A continuous fiber reinforced prepreg and a preparation method thereof are provided.
[0006] The main objectives of the present invention are: 1. To achieve efficient and uniform spreading of fiber filaments in a prepreg tape.
[0007] 2. Improve the impregnation efficiency and uniformity of molten resin.
[0008] 3. Accurately control the resin content and the stability of the prepreg tape size.
[0009] 4. Effectively improve the comprehensive mechanical properties and weather resistance of prepreg tapes.
[0010] To achieve the above objectives, the present invention adopts the following technical solutions.
[0011] A method for preparing a continuous fiber reinforced prepreg tape comprises: 1) pretreating matrix fibers to obtain pretreated fibers.
[0012] 2) The pretreated fibers are subjected to an air-flow spinning method to obtain a continuous fiber thin layer tape.
[0013] 3) The continuous fiber thin layer tape is subjected to segmented impregnation and reinforcement treatment, and then cooled and shaped to obtain a continuous fiber reinforced prepreg tape.
[0014] Preferably, in step 1), the matrix fiber is carbon fiber; the carbon fiber is a mixed fiber of continuous long fiber and short-cut fiber; the continuous long fiber is ≥200 m; and the short-cut fiber is 5 to 15 mm in length.
[0015] Preferably, the proportion of the chopped fibers in the matrix fibers is 12 to 18 wt%.
[0016] Preferably, the pretreatment process in step 1) is as follows: the modified impregnation material is dissolved in a concentrated sulfuric acid solution to prepare a pretreatment liquid, the pretreatment liquid is evenly atomized and sprayed on the base fiber, and after standing for 5 to 10 minutes, it is washed with deionized water and dried; the concentrated sulfuric acid is industrial concentrated sulfuric acid with a sulfuric acid degree of ≥70 wt%; the concentration of the modified impregnation material in the pretreatment liquid is 5 to 8 wt%; the amount of the pretreatment liquid is 8 to 10 wt% of the base fiber.
[0017] Preferably, in step 2), during the yarn spreading process, the air flow temperature is controlled to be 350-380° C. and the air flow velocity is controlled to be 3-5 m / s.
[0018] Preferably, in step 3), the segmented impregnation process is to place the continuous fiber thin layer tape in a protective atmosphere and perform impregnation treatment under the conditions of melt-modified prepreg impregnation; the segmented impregnation is divided into an initial motion impregnation and a final penetration impregnation; in the initial motion impregnation process, the pulling rate of the continuous fiber thin layer tape in the melt-modified prepreg is controlled to be 3 to 5 m / min, and an intermediate prepreg is obtained after impregnation, and the matrix fiber mass content in the intermediate prepreg is 92 to 95 wt%; in the final penetration impregnation process, the pulling rate of the intermediate prepreg in the melt-modified prepreg is controlled to be 1.5 to 2.5 m / min, and a semi-finished prepreg is obtained after impregnation, and the matrix fiber mass content in the semi-finished prepreg is 68 to 72 wt%.
[0019] Preferably, the modified impregnation material is composed of modified polyetheretherketone, maleic anhydride grafted compatibilizer, antioxidant B215 and N, N-hexylene bis stearamide in a mass ratio of 50:1.5:1.5:0.1, and the modified polyetheretherketone is heated to just melt and then the other ingredients are added and mixed evenly to obtain the modified impregnation material; the modified polyetheretherketone is prepared by the following method: polyetheretherketone and 95-98 wt% concentrated sulfuric acid are mixed evenly in a mass ratio of 1: (0.8-1.2), reacted at a temperature of 55-65 ° C for 1.75-2.25 h, dialyzed with ionized water to a pH of 6.8-7.2, and vacuum dried to prepare sulfonated polyetheretherketone; sulfonated polyetheretherketone and modifier are mixed evenly in a mass ratio of 1: (0.4-0.6), and heated at a temperature of 340-360 ° C and a screw speed of 80-90 The modified polyetheretherketone was prepared by melt blending in a twin-screw extruder at rpm.
[0020] The modifier is furan and N, N'-(4, 4'-methylenediphenyl) bismaleimide, which are mixed evenly in a mass ratio of 1: (1.75-1.95).
[0021] Preferably, during the cooling and shaping process in step 3), the relative humidity of the environment is controlled to be ≤30%.
[0022] A continuous fiber reinforced prepreg tape.
[0023] The core of the technical solution of the present invention lies in the organic combination of air-flow yarn spreading technology and immersion plating technology.
[0024] In the air flow yarn spreading process, the present invention abandons the traditional mechanical rolling or tension control method and instead adopts high-pressure airflow to implement non-contact spreading of fiber bundles, which can effectively avoid problems such as fiber damage and local stress concentration that may be caused by traditional methods, and provide better fiber basic conditions for subsequent process flows.
[0025] However, it was also discovered during the early research and development process that simply combining air-flow yarn spreading technology with immersion plating technology would lead to a huge distribution difference in the mechanical properties of the prepreg tape. It performed well on the X-axis, but poorly on the Y-axis. This was mainly because air-flow yarn spreading could indeed significantly improve the uniformity of fiber distribution, but its axial distribution was too single. After being prepared into a prepreg tape using immersion plating technology, its Y-axis performance was mainly provided by the curing of the impregnated material, resulting in a more significant uneven distribution of its mechanical properties.
[0026] Therefore, the present invention adopts a special processing method so that the airflow yarn spreading technology and the impregnation technology in the preparation process can be more effectively combined. In this process, the first and most important thing is the pretreatment of the matrix fiber, that is, the carbon fiber used in the present invention. Generally speaking, airflow yarn prepreg tapes are usually only carried out using continuous long fibers, because short fibers are easy to gather together in the airflow and are difficult to disperse evenly like long fibers, resulting in poor yarn spreading effect and inability to form a uniform fiber layer. At the same time, short fibers are easy to entangle and knot with each other in the airflow, forming clumps, which affects the uniformity and continuity of the yarn spreading. On the other hand, since the short fibers are shorter in length, they are more susceptible to the impact and friction of the airflow in the airflow, which can easily lead to fiber breakage and an increase in lint, reducing the strength and quality of the fibers. They may also be repeatedly folded and bent, further aggravating the damage to the fibers and affecting the mechanical properties.
[0027] However, in the present invention, a pretreatment method is used before air-spinning. After partially dissolving the impregnated material of the present invention with commercially available 70 wt% industrial concentrated sulfuric acid, a highly fluid pretreatment solution is formed and then sprayed onto the surface of the matrix fibers to evenly wet them. This process can produce a "distributed point treatment" on the fibers. This is because in addition to the impregnation treatment, the concentrated acid in the pretreatment solution can actually change the surface properties of the matrix carbon fibers to a certain extent, especially in terms of polarity.
[0028] Carbon fiber is one of the preferred fibers for air-flow yarn spreading technology because non-polar or weakly polar fibers are more suitable for air-flow yarn spreading technology and are not easy to agglomerate or clump. After pretreatment by the present invention, the polarity of the carbon fiber surface can actually be changed to a certain extent. Under appropriate concentrations of concentrated sulfuric acid and appropriate treatment conditions, some polar functional groups, such as carbonyl and carboxyl groups, will be introduced into the carbon fiber surface, thereby increasing the surface energy and wettability of the carbon fiber. This can further improve the bonding strength between the carbon fiber and the modified preservative. Secondly, a uniform "polar point" can be formed as a linking point to realize the linking of long and short fibers, and the linking point can be used as the "axis" to connect the short fibers in the air. The movement characteristics during the flow yarn spreading process change the distribution form of the matrix fibers, ensuring that several Y-axis links can be formed between the long fibers while allowing the short fibers to be evenly distributed between the long fibers and distributed in an oblique or even vertical manner, thereby enhancing the Y-axis linking effect. At the same time, the pretreatment time is controlled appropriately to avoid significant oxidative damage to the fibers, which leads to a decrease in their mechanical properties. At the same time, the initial fixation of the modified impregnated material can be achieved. This fixation is not to solidify and coat it on the fiber surface, but to "protect" the polar linking points while pretreating the matrix carbon fibers with oxidizing concentrated acid to achieve initial Y-axis strengthening.
[0029] Of course, this process also requires coordinated improvements to the air flow yarn spreading process. During the air flow yarn spreading process, the present invention draws on the operation method of hot air pre-spreading fiber, and uses hot air flow as the yarn spreading air flow. This can make the axiality of long fiber yarn spreading better, reduce local fiber enrichment and stress concentration, and effectively and naturally distribute short fibers, thereby improving the product yield and average performance.
[0030] The present invention then adjusts the impregnation process. A segmented impregnation process is employed, with different pulling rates applied during each step (note: the pulling direction is along the axial direction of the long fibers). This is because the pretreatment process and the preceding air-flow yarn spreading process combine to achieve a certain degree of oblique distribution of the short fibers in the continuous fiber thin layer. During the initial motion impregnation process, the Y-axis distribution trend of the short fibers is further enhanced, while the prepreg initially coats and fixes the long and short fibers. A final penetration impregnation process, similar to conventional impregnation, then achieves effective and complete coating and fixation of the prepreg, resulting in the finished prepreg.
[0031] But the present invention goes beyond this. Another key point is the improvement and optimization of the prepreg. Specifically, the thermoplastic resin is subjected to an organic treatment. By introducing polar functional groups through sulfonation modification and a dynamic crosslinker to construct a reversible network and guide function, the performance of the resin material can be effectively enhanced. The organic functional groups form a crosslinked network with the polar groups on the fiber surface, effectively strengthening the mechanical properties of the resin material. The organic treatment of polyetheretherketone achieves strong constraint and uniform distribution of the fibers at the molecular level. The synergistic effect of chemical bonds (hydrogen bonds, covalent bonds, and dynamic bonds) significantly enhances the prepreg's interfacial strength, moisture and heat resistance, and functional properties, ensuring its high performance in extreme environments.
[0032] Polyetheretherketone (PEEK) is a semicrystalline, high-performance thermoplastic polymer with a backbone composed of alternating benzene rings, ether bonds, and ketone groups, endowing it with excellent high-temperature resistance, chemical stability, and mechanical strength. However, unmodified PEEK has low polarity and weak interfacial bonding with non-polar or weakly polar fibers (such as carbon fibers), resulting in insufficient interlaminar shear strength in the composite material. The present invention introduces specific functional groups and chemical bonds through organic treatment, significantly enhancing interfacial bonding and optimizing fiber distribution.
[0033] In this invention, polyetheretherketone (PEEK) is dissolved in concentrated sulfuric acid, and sulfonic acid groups are introduced onto the benzene rings through an electrophilic substitution reaction. Leveraging the strong polarity of the sulfonic acid groups, the wettability of the resin and fiber surfaces is significantly improved. After sulfonation, the sulfonic acid protons within the resin matrix can form hydrogen bonds with the hydroxyl groups on the fiber surface, enhancing the bond strength between the matrix and the fiber through electrostatic bonding in an alkaline environment. Furthermore, the polar groups reduce water adsorption at the interface through chemical bonding, resulting in the material retaining a high level of strength after wet-heat aging.
[0034] The modified polyetheretherketone matrix and the fiber interface in the present invention play the role of transferring load, effectively connecting groups and reinforcing bodies. In conventional technology, the interface between the substrate and the fiber is the weak link in the fracture process of the fiber prepreg. In the present invention, the conjugated diene between maleimide and furan can form a cycloolefin skeleton with the dienophile in a relatively low temperature environment, thereby strengthening the connection strength of the modified polyetheretherketone matrix to the continuous fiber. In addition, in a high-temperature use environment, the viscosity of the resin in the prepreg is reduced, the fiber produces a large displacement, and the cycloolefin skeleton can open to form an effective carbon chain, allowing the fiber to be stretched and arranged under shear force, ensuring the chemical connection between the substrate and the fiber, and improving the tensile strength of the prepreg in extreme environments. After cooling, the cycloolefin skeleton is restored to form a cross-linked network to fix the fiber position.
[0035] The beneficial effects of the present invention are as follows: the present invention enhances the Y-axis bonding strength of the prepreg tape and improves the fiber distribution form from a microscopic level through the organic combination of air-flow yarn spreading and impregnation technology, so that the overall mechanical properties of the prepreg tape are significantly improved and optimized, and the weather resistance of the prepreg tape is also significantly improved through the improvement of the impregnation material processing. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only a portion of the embodiments of the present invention, rather than all of the embodiments. Therefore, all other embodiments derived by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0037] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0038] Unless otherwise specified, the continuous carbon fiber used in the embodiments of the present invention has a length of 220 to 250 m, and the chopped carbon fiber has a length of 5 to 15 mm, and both are high-quality carbon fibers with a tensile strength of 3600 to 3800 MPa.
[0039] Example 1: A method for preparing a continuous fiber reinforced prepreg, the method comprising: 1) preparing a modified prepreg, wherein the modified prepreg is composed of a mixture of modified polyetheretherketone, a maleic anhydride grafted compatibilizer, an antioxidant B215 and N,N-hexylene bisstearamide in a mass ratio of 50:1.5:1.5:0.1, heating the modified polyetheretherketone until it is just melted, adding other ingredients and mixing them evenly to obtain the modified prepreg.
[0040] The modified polyetheretherketone is prepared by the following method: polyetheretherketone and 96 wt% concentrated sulfuric acid are uniformly mixed in a mass ratio of 1:1, reacted at a temperature of 62°C for 2 hours, dialyzed with deionized water to a pH of 7, and vacuum dried to prepare sulfonated polyetheretherketone.
[0041] Sulfonated polyetheretherketone and a modifier were uniformly mixed in a mass ratio of 1:0.5, and melt-blended in a twin-screw extruder at a temperature of 350°C and a screw speed of 85 rpm to prepare modified polyetheretherketone.
[0042] The modifier is furan and N, N'-(4, 4'-methylenediphenyl) bismaleimide, which are uniformly mixed in a mass ratio of 1:1.8.
[0043] 2) Carbon fiber continuous fibers and carbon fiber chopped fibers with a mass ratio of 85:15 were used as matrix fibers. The continuous fibers were unfolded and the chopped fibers were evenly spread on the surface of the continuous fibers for pretreatment. During the pretreatment process, modified polyetheretherketone was dissolved in 70wt% concentrated sulfuric acid solution to prepare a pretreatment solution with a modified polyetheretherketone concentration of 6.5wt%. The pretreatment solution was evenly atomized and sprayed on the matrix fibers. The amount of pretreatment solution was 8wt% of the matrix fibers. After standing for 10 min, the fibers were washed with deionized water and dried to obtain pretreated fibers.
[0044] 3) The pretreated fibers were spread by an air-flow spreading method. During the air-flow spreading process, the air temperature was controlled at 355 ℃ and the air velocity was controlled at 4 m / s to obtain a continuous fiber thin layer tape.
[0045] 4) performing a segmented impregnation reinforcement treatment on the continuous fiber thin layer tape; the segmented impregnation is divided into an initial kinematic impregnation and a final infiltration impregnation; in the initial kinematic impregnation process, the continuous fiber thin layer tape is pulled into the molten modified prepreg at 355-360°C at a rate of 4.5 m / min, and an intermediate prepreg tape is obtained after impregnation, wherein the matrix fiber mass content of the intermediate prepreg tape is 93.1 wt%; in the final infiltration impregnation process, the intermediate prepreg tape is pulled into the molten modified prepreg at 355-360°C at a rate of 2 m / min, and a semi-finished prepreg tape is obtained after impregnation, wherein the matrix fiber mass content of the semi-finished prepreg tape is 69.6 wt%; and the continuous fiber reinforced prepreg tape is then naturally cooled and shaped in an environment with a relative humidity of ≤30%.
[0046] The fiber-reinforced prepreg prepared in this example was subjected to performance testing, and the specific characterization results are as follows.
[0047] Air-flow yarn uniformity test: The fiber layer after the yarn is spread in step (1) of the embodiment is cross-sectioned, and the single-filament distribution is observed using a scanning electron microscope (SEM). Ten points are randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber are measured. The coefficient of variation (cv%) of the continuous long fiber is calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0048] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 meter of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0049] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0050] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0051] The performance test results are shown in Table 1 below.
[0052] Table 1: Example 1 sample performance test results:
[0053] The characterization results in Table 1 above clearly demonstrate the remarkable performance advantages of the prepreg tape of the present invention. The coefficient of variation is extremely low, indicating that the continuous long fibers are distributed uniformly and spread very smoothly. The connection points formed during pretreatment can maintain excellent axial spread and lateral alignment during the hot air flow yarn spreading process. This is primarily due to the fact that the small amount of impregnated material at the connection points softens or even melts to form droplets under the temperature conditions of the hot air flow yarn spreading process. The tension of the droplets and the polarity of the fibers allow the long fiber connection points to slide along their axial direction, achieving straightness and reducing bending. This also prevents the originally uniformly connected short fibers from being affected and enriched. However, excessively high hot air temperatures should be avoided, as they can cause the short fibers to agglomerate and clumping, which in turn increases the coefficient of variation and reduces mechanical properties. The extremely low dry spot rate also demonstrates the good plating effect. Furthermore, the mechanical properties are extremely excellent. Generally speaking, the resin matrix in the prepreg will form a certain structure after curing, and its performance has an important influence on the strength of the composite material. Although the resin can enhance the mechanical properties of the fiber, improve the toughness, impact resistance and environmental stress cracking resistance of the composite material, the strength of the resin matrix is relatively low compared to the high strength of the carbon fiber itself, which will reduce the overall axial tensile strength to a certain extent. For example, the UD unidirectional tape prepreg prepared from the commercially available IMS65 carbon fiber has a fiber tensile strength of about 5800 MPa, while the X-axis tensile strength of its product is about 2900 MPa, and the Y-axis tensile strength is only about 90-102 MPa. The tensile strength of the X-axis is only about 50% of the original carbon fiber, while the present invention is as high as 73.4-77.5%, which shows that the modified prepreg used in the present invention is far superior to the commercially available prepreg, and its combination effect is better, and it can better form the effect of transferring the load and thus show a higher performance retention rate. In theory, using better quality carbon fiber can show extremely superior tensile strength performance. Even more significantly improved is the Y-axis tensile strength. The Y-axis tensile strength of existing carbon fiber prepregs is generally only 90 to 110 MPa, while the present invention achieves more than ten times the performance. This is due to the synergistic combination of pretreatment, hot air yarn spreading, and segmented dip-plating in the present invention, which achieves a special distribution of short fibers and significantly enhances the Y-axis tensile strength. Its tensile strength can reach approximately 28.7 to 30.3% of the original fiber tensile strength, far higher than the tensile strength of modified polyetheretherketone, indicating that the short fibers do play a tensile reinforcement role in the Y-axis direction, demonstrating the effectiveness of the solution. In addition to optimizing the mechanical properties of the material, the modified polyetheretherketone also exhibits extremely excellent weather resistance, with the overall strength retention rate even reaching over 95% after aging experiments.
[0054] Example 2: A method for preparing a continuous fiber reinforced prepreg, the method comprising: 1) preparing a modified prepreg, wherein the modified prepreg is composed of a mixture of modified polyetheretherketone, a maleic anhydride grafted compatibilizer, an antioxidant B215 and N,N-hexylene bisstearamide in a mass ratio of 50:1.5:1.5:0.1, heating the modified polyetheretherketone until it is just melted, adding other ingredients and mixing them evenly to obtain the modified prepreg.
[0055] The modified polyetheretherketone is prepared by the following method: polyetheretherketone and 98 wt% concentrated sulfuric acid are uniformly mixed in a mass ratio of 1:0.8, reacted at a temperature of 55°C for 2.25 hours, dialyzed with deionized water to a pH of 6.8, and vacuum dried to prepare sulfonated polyetheretherketone.
[0056] Sulfonated polyetheretherketone and a modifier were uniformly mixed in a mass ratio of 1:0.4, and melt-blended in a twin-screw extruder at a temperature of 340°C and a screw speed of 80 rpm to prepare modified polyetheretherketone.
[0057] The modifier is furan and N, N'-(4, 4'-methylenediphenyl) bismaleimide, which are uniformly mixed in a mass ratio of 1:1.75.
[0058] 2) Carbon fiber continuous fibers and carbon fiber chopped fibers with a mass ratio of 82:18 were used as matrix fibers. The continuous fibers were unfolded and the chopped fibers were evenly spread on the surface of the continuous fibers for pretreatment. During the pretreatment process, modified polyetheretherketone was dissolved in 70 wt% concentrated sulfuric acid solution to prepare a pretreatment solution with a modified polyetheretherketone concentration of 8.0 wt%. The pretreatment solution was evenly atomized and sprayed on the matrix fibers. The amount of pretreatment solution was 10.0 wt% of the matrix fibers. After standing for 5 min, the pretreated fibers were washed with deionized water and dried to obtain pretreated fibers.
[0059] 3) The pretreated fibers were subjected to air-flow spinning. During the air-flow spinning process, the air temperature was controlled at 350 °C and the air velocity was controlled at 3 m / s to obtain a continuous fiber thin layer tape.
[0060] 4) performing a segmented impregnation reinforcement treatment on the continuous fiber thin layer tape; the segmented impregnation is divided into an initial kinematic impregnation and a final infiltration impregnation; in the initial kinematic impregnation process, the continuous fiber thin layer tape is pulled into the molten modified prepreg at 355-360°C at a rate of 3 m / min, and an intermediate prepreg tape is obtained after impregnation, wherein the matrix fiber mass content of the intermediate prepreg tape is 92.6 wt%; in the final infiltration impregnation process, the intermediate prepreg tape is pulled into the molten modified prepreg at 355-360°C at a rate of 1.5 m / min, and a semi-finished prepreg tape is obtained after impregnation, wherein the matrix fiber mass content of the semi-finished prepreg tape is 70.2 wt%; and then naturally cooling and shaping in an environment with a relative humidity of ≤30% to obtain a continuous fiber reinforced prepreg tape.
[0061] The fiber-reinforced prepreg prepared in this example was subjected to performance testing, and the specific characterization results are as follows.
[0062] Air-flow yarn uniformity test: The fiber layer after the yarn is spread in step (1) of the embodiment is cross-sectioned, and the single-filament distribution is observed using a scanning electron microscope (SEM). Ten points are randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber are measured. The coefficient of variation (cv%) of the continuous long fiber is calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0063] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 m of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0064] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0065] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0066] The performance test results are shown in Table 2 below.
[0067] Table 2: Example 2 sample performance test results:
[0068] From the characterization results in Table 2 above, it can be seen that the present invention uses more modified impregnation materials in the pretreatment process, which further enhances the initial linking effect, resulting in further optimization and improvement of the tensile strength of the Y axis, but a more significant decrease in the X axis strength, and the resulting coefficient of variation and dry spot rate also increase. It can be seen that the pretreatment process has a significant impact on the straightness, smoothness, distribution uniformity and mechanical properties of the continuous long fibers of the product.
[0069] Example 3: A method for preparing a continuous fiber reinforced prepreg, the method comprising: 1) preparing a modified prepreg, wherein the modified prepreg is composed of a mixture of modified polyetheretherketone, a maleic anhydride grafted compatibilizer, an antioxidant B215 and N,N-hexylene bisstearamide in a mass ratio of 50:1.5:1.5:0.1, heating the modified polyetheretherketone until it is just melted, adding other ingredients and mixing them evenly to obtain the modified prepreg.
[0070] The modified polyetheretherketone is prepared by the following method: polyetheretherketone and 95 wt% concentrated sulfuric acid are uniformly mixed in a mass ratio of 1:1.2, reacted at a temperature of 65°C for 1.75 hours, dialyzed with deionized water to a pH of 7.2, and vacuum dried to prepare sulfonated polyetheretherketone.
[0071] Sulfonated polyetheretherketone and a modifier were uniformly mixed in a mass ratio of 1:0.6, and melt-blended in a twin-screw extruder under environmental conditions of a temperature of 360°C and a screw speed of 90 rpm to prepare modified polyetheretherketone.
[0072] The modifier is furan and N, N'-(4, 4'-methylenediphenyl) bismaleimide, which are uniformly mixed in a mass ratio of 1:1.95.
[0073] 2) Carbon fiber continuous fibers and carbon fiber chopped fibers with a mass ratio of 88:12 were used as matrix fibers. The continuous fibers were unfolded and the chopped fibers were evenly spread on the surface of the continuous fibers for pretreatment. During the pretreatment process, modified polyetheretherketone was dissolved in 70 wt% concentrated sulfuric acid solution to prepare a pretreatment solution with a modified polyetheretherketone concentration of 5.0 wt%. The pretreatment solution was evenly atomized and sprayed on the matrix fibers. The amount of pretreatment solution was 8 wt% of the matrix fibers. After standing for 10 min, the fibers were washed with deionized water and dried to obtain pretreated fibers.
[0074] 3) The pretreated fibers were subjected to air-flow spinning. During the air-flow spinning process, the air temperature was controlled at 360 °C and the air velocity was controlled at 5 m / s to obtain a continuous fiber thin layer tape.
[0075] 4) performing a segmented impregnation reinforcement treatment on the continuous fiber thin layer tape; the segmented impregnation is divided into an initial kinematic impregnation and a final infiltration impregnation; in the initial kinematic impregnation process, the continuous fiber thin layer tape is pulled into the molten modified prepreg at 355-360°C at a rate of 4.5 m / min, and an intermediate prepreg tape is obtained after impregnation, wherein the matrix fiber mass content of the intermediate prepreg tape is 92.9 wt%; in the final infiltration impregnation process, the intermediate prepreg tape is pulled into the molten modified prepreg at 355-360°C at a rate of 2 m / min, and a semi-finished prepreg tape is obtained after impregnation, wherein the matrix fiber mass content of the semi-finished prepreg tape is 69.9 wt%; and then naturally cooling and setting in an environment with a relative humidity of ≤30% to obtain a continuous fiber reinforced prepreg tape.
[0076] The fiber-reinforced prepreg prepared in this example was subjected to performance testing, and the specific characterization results are as follows.
[0077] Air-flow yarn uniformity test: The fiber layer after the yarn is spread in step (1) of the embodiment is cross-sectioned, and the single-filament distribution is observed using a scanning electron microscope (SEM). Ten points are randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber are measured. The coefficient of variation (cv%) of the continuous long fiber is calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0078] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 m of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0079] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0080] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0081] The performance test results are shown in Table 3 below.
[0082] Table 3: Example 3 sample performance test results:
[0083] From the characterization results in Table 3 above, we can see that the modified impregnation material used in the pretreatment process was relatively reduced in this example. This did not significantly affect the product's coefficient of variation, dry spot rate, and X-axis tensile strength, but did have a significant impact on the Y-axis tensile strength. This shows that the pretreatment process is extremely critical for achieving good Y-axis tensile performance.
[0084] Comparative Example 1: Based on Example 1, this example does not perform the pretreatment described in step 2), and is compared horizontally with Example 1. Specifically, the following comparative groups are set.
[0085] Table 4: Horizontal comparison of the preparation processes of Comparative Example 1 and Example 1:
[0086] The same experimental characterization was performed on the products of each group mentioned above, specifically including: air-flow yarn uniformity detection: the fiber layer after the yarn was spread in step (1) of the embodiment was cross-sectioned, and the single-filament distribution was observed using a scanning electron microscope (SEM). Ten points were randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber were measured. The coefficient of variation (cv%) of the continuous long fiber was calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0087] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 m of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0088] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0089] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0090] The performance test results are shown in Table 5 below.
[0091] Table 5: Comparative Example 1 sample performance test results:
[0092] It can be clearly seen from the characterization results in Table 5 above that the pretreatment process of the present invention has a very significant impact on first achieving the initial distribution and fixation of long and short fibers. If effective pretreatment is not performed, then the subsequent steps are the same as in Example 1, and there will be extremely large performance differences. Although the difference in the X-axis is relatively small, the performance difference in the Y-axis is as high as several times.
[0093] Comparative Example 2: Based on Example 1, this example controls the air-flow yarn spreading process in step 3) and conducts a horizontal comparison. Specifically, the following comparison groups are set.
[0094] Table 6: Horizontal comparison of the preparation processes of Comparative Example 2 and Example 1:
[0095] The same experimental characterization was performed on the products of each group mentioned above, specifically including: air-flow yarn uniformity detection: the fiber layer after the yarn was spread in step (1) of the embodiment was cross-sectioned, and the single-filament distribution was observed using a scanning electron microscope (SEM). Ten points were randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber were measured. The coefficient of variation (cv%) of the continuous long fiber was calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0096] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 m of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0097] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0098] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0099] The performance test results are shown in Table 7 below.
[0100] Table 7: Comparative Example 2 sample performance test results:
[0101] It can be clearly seen from the characterization results in Table 7 above that the use of room temperature airflow for airflow yarn spreading will lead to a significant increase in the coefficient of variation of the product's distribution uniformity, an increase in the dry spot rate, and a sharp decrease in the X-axis tensile strength. However, due to the possibility of more obliquely distributed fibers or the entanglement and distortion of continuous long fibers, the Y-axis tensile support effect is generated, but this comprehensive performance obviously does not meet the expected performance of the present invention. The use of slightly lower temperatures for hot air airflow yarn spreading also has similar problems, but the relative degree is alleviated. The use of too high a temperature for hot air airflow yarn spreading significantly affects the distribution of short fibers, which may produce less agglomeration and agglomeration, resulting in a slight increase in the coefficient of variation. Although the X-axis tensile strength decreases slightly and is still at a relatively good level, the Y-axis tensile strength decreases significantly. It can be seen that the temperature has a more significant effect on it during the airflow yarn spreading process.
[0102] Comparative Example 3: Based on Example 1, this example controls the impregnation process in step 4) for horizontal comparison, specifically setting the following comparison groups.
[0103] Table 8: Horizontal comparison of the preparation processes of Comparative Example 3 and Example 1:
[0104] The same experimental characterization was performed on the products of each group mentioned above, specifically including: air-flow yarn uniformity detection: the fiber layer after the yarn was spread in step (1) of the embodiment was cross-sectioned, and the single-filament distribution was observed using a scanning electron microscope (SEM). Ten points were randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber were measured. The coefficient of variation (cv%) of the continuous long fiber was calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0105] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 m of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0106] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0107] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0108] The performance test results are shown in Table 9 below.
[0109] Table 9: Comparative Example 3 sample performance test results:
[0110] It can be clearly seen from the characterization results in Table 9 above that the immersion plating process, as a core process of the technical solution of the present invention, also has a significant impact on the performance of the product. Segmented immersion plating is a key process for controlling the distribution of long and short fibers. Using too small an initial pulling rate will cause the distribution form and axial direction of the short fibers to deviate from the expected target after the initial coating and fixation. However, too large a pulling rate may cause the continuous long fibers to curl or even stage. For conventional continuous fiber thin layer tapes, the effect of too large a pulling rate is not significant. However, for the continuous fiber thin layer tape of the present invention, due to the generation of link points during the pretreatment process, too large a pulling rate may cause the nodes to approach each other, and the fibers between the nodes to bend, resulting in a significant decrease in performance.
[0111] Comparative Example 4: Based on Example 1, this example only adjusts the impregnation material.
[0112] Table 10: Horizontal comparison of the preparation processes of Comparative Example 4 and Example 1:
[0113] The same experimental characterization was performed on the products of each group mentioned above, specifically including: air-flow yarn uniformity detection: the fiber layer after the yarn was spread in step (1) of the embodiment was cross-sectioned, and the single-filament distribution was observed using a scanning electron microscope (SEM). Ten points were randomly selected along the axial direction of the continuous long fiber, and the standard deviation (σ) and the average value (z) of the spread width of the continuous long fiber were measured. The coefficient of variation (cv%) of the continuous long fiber was calculated by combining the standard deviation of the spread width with the average value of the spread width. The specific calculation formula is: .
[0114] Resin impregnation efficiency: 3D imaging of the prepreg was performed to analyze the resin penetration rate within the fiber bundles. Randomly sample 1 m of prepreg tape and calculate the percentage of dry spots (areas not covered by resin).
[0115] Mechanical properties testing: The X-axis and Y-axis tensile strength of the prepreg are characterized and tested respectively.
[0116] Durability test in hot and humid environment: The fiber-reinforced prepreg prepared in this example was aged for 500 h at a temperature of 85°C and an ambient humidity of 85%, and the mechanical property retention rate was tested.
[0117] The performance test results are shown in Table 11 below.
[0118] Table 11: Comparative Example 4 sample performance test results:
[0119] The characterization results in Table 11 clearly show that the modified polyetheretherketone of the present invention has a significant impact on product performance. Because polyetheretherketone itself has limited bonding strength with carbon fibers, it struggles to effectively transfer loads and provide reinforcement. Furthermore, its weather resistance is far weaker than that of the modified polyetheretherketone constructed in the present invention, leading to a sharp decrease in strength retention after wet-heat aging.
[0120] From the above, it can be clearly seen that for the technical solution of the present invention, in order to prepare high-quality products, effective optimization is achieved through the coordinated cooperation of pretreatment, hot air flow yarn spreading and segmented immersion plating.
Claims
1. A method for preparing a continuous fiber reinforced prepreg tape, characterized in that: The method comprises: 1) pre-treating matrix fibers to obtain pre-treated fibers; 2) performing a yarn spreading process on the pre-treated fibers by an air-flow yarn spreading method to obtain a continuous fiber thin layer tape; 3) performing a segmented impregnation reinforcement process on the continuous fiber thin layer tape, and then cooling and shaping the continuous fiber thin layer tape to obtain a continuous fiber reinforced prepreg tape; the pre-treatment process in step 1 comprises: dissolving a modified impregnation material in a concentrated sulfuric acid solution to prepare a pre-treatment liquid, uniformly atomizing and spraying the pre-treatment liquid on the matrix fibers, standing for 5 to 10 minutes, and then washing with deionized water and drying; the segmented impregnation process in step 3 comprises placing the continuous fiber thin layer tape in a protective atmosphere and performing an impregnation process under the conditions of a melted modified impregnation material; the modified impregnation material comprises modified polyetheretherketone.
2. The method for preparing a continuous fiber reinforced prepreg tape according to claim 1, characterized in that: Step 1) The matrix fiber is carbon fiber; the carbon fiber is a mixed fiber of continuous long fiber and short-cut fiber; the continuous long fiber is ≥200 m; and the short-cut fiber is 5 to 15 mm in length.
3. The method for preparing a continuous fiber reinforced prepreg tape according to claim 2, characterized in that: The proportion of the short-cut fibers in the matrix fibers is 12 to 18 wt %.
4. The method for preparing a continuous fiber reinforced prepreg tape according to claim 1, characterized in that: Step 1) During the pretreatment process: the concentrated sulfuric acid is industrial concentrated sulfuric acid with a sulfuric acid degree of ≥70 wt%; the concentration of the modified impregnated material in the pretreatment solution is 5-8 wt%; and the amount of the pretreatment solution used is 8-10 wt% of the base fiber.
5. The method for preparing a continuous fiber reinforced prepreg tape according to claim 1, characterized in that: In step 2), during the yarn spreading process, the air flow temperature is controlled to be 350-380° C. and the air flow velocity is controlled to be 3-5 m / s.
6. The method for preparing a continuous fiber reinforced prepreg tape according to claim 1, characterized in that: In step 3), the segmented impregnation is divided into an initial motion impregnation and a final penetration impregnation; in the initial motion impregnation process, the pulling rate of the continuous fiber thin layer tape in the molten modified prepreg is controlled to be 3 to 5 m / min, and an intermediate prepreg is obtained after impregnation, and the matrix fiber mass content in the intermediate prepreg is 92 to 95 wt%; in the final penetration impregnation process, the pulling rate of the intermediate prepreg in the molten modified prepreg is controlled to be 1.5 to 2.5 m / min, and a semi-finished prepreg is obtained after impregnation, and the matrix fiber mass content in the semi-finished prepreg is 68 to 72 wt%.
7. The method for preparing a continuous fiber reinforced prepreg tape according to claim 1, characterized in that: The modified impregnation material is prepared by the following method: polyetheretherketone and 95-98 wt% concentrated sulfuric acid are uniformly mixed in a mass ratio of 1: (0.8-1.2), reacted under environmental conditions of a temperature of 55-65°C for 1.75-2.25 hours, dialyzed with deionized water to a pH of 6.8-7.2, and vacuum dried to prepare sulfonated polyetheretherketone; the sulfonated polyetheretherketone and a modifier are uniformly mixed in a mass ratio of 1: (0.4-0.6), and melt-blended in a twin-screw extruder under environmental conditions of a temperature of 340-360°C and a screw speed of 80-90 rpm to prepare the modified polyetheretherketone; the modifier is furan and N,N'-(4,4'-methylenediphenyl)bismaleimide, uniformly mixed in a mass ratio of 1: (1.75-1.95).
8. The method for preparing a continuous fiber reinforced prepreg tape according to claim 1, characterized in that: During the cooling and shaping process in step 3), the relative humidity of the environment is controlled to be ≤30%.
9. A continuous fiber reinforced prepreg tape produced by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Biological material with antibacterial and osteoblastic integration performance as well as preparation method and application of biological material
CN112898619A
Continuous fiber reinforced thermoplastic composite material as well as preparation method and application thereof
CN114292490A
Modified fiber reinforced PEEK bone scaffold material and preparation method thereof
CN118105538A
Sandwich structure and integrally formed article using the same, and methods for production thereof
US20160214346A1
Modified continuous carbon fiber reinforced polyether ether ketone composite material laminated plate and preparation method therefor
WO2024027527A1
Cited By
Prepreg resin infiltration uniformity analysis method and system based on microscopic image
CN121600507A